Pain Reduction after Caesarean Section through Lavender Aromatherapy - Gusnita, Sintia; Arsi, Ranida; Wisudawati, Eka Rora Suci (Jurnal Keperawatan Profesional (KEPO), 2025)
Pain is a common problem experienced by patients after undergoing a cesarean section. Lavender aromatherapy, which contains active compounds such as linalool and linalyl, was believed to reduce pain due to its analgesic properties and its ability to stimulate the release of endorphins by activating the hypothalamus. The aim of this study was to determine the effectiveness of lavender aromatherapy in reducing post-cesarean section pain at Siti Fatimah Az-Zahra Regional Public Hospital, South Sumatra Province. This study was a quantitative research with a quasi-experimental design using a non-equivalent control group approach. A total of 54 post-cesarean section mothers were selected as participants, with 27 assigned to the experimental group and 27 to the control group. Pain intensity was measured using the Numeric Rating Scale (NRS). Sampling was conducted using a purposive sampling technique, and data were analyzed using the Wilcoxon test. The results of the Wilcoxon test showed a p-value of 0,000 (p-value<0,05), indicating a significant decrease in post-cesarean section pain following lavender aromatherapy intervention. Lavender aromatherapy can be considered a complementary therapy option for managing postoperative pain after cesarean section.